Skew-Zigzag Algebras - Couture, C. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
We investigate the skew-zigzag algebras introduced by Huerfano and Khovanov. In particular, we relate moduli spaces of such algebras with the cohomology of the corresponding graph.